2021
DOI: 10.3389/fpsyg.2021.669481
|View full text |Cite
|
Sign up to set email alerts
|

Generalization and False Memory in an Acquired Equivalence Paradigm: The Influence of Physical Resemblance Across Related Episodes

Abstract: The ability to make inferences about related experiences is an important function of memory that allows individuals to build generalizable knowledge. In some cases, however, making inferences may lead to false memories when individuals misremember inferred information as having been observed. One factor that is known to increase the prevalence of false memories is the physical resemblance between new and old information. The extent to which physical resemblance has parallel effects on generalization and memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In the yoked task version, each quadruplet was yoked to another quadruplet to serve as each other's foils (Bowman et al, 2021;de Araujo Sanchez and Zeithamova, 2023). This meant that the foil for each face was the same across all repetitions of the same trial type.…”
Section: Yoked Conditionmentioning
confidence: 99%
“…In the yoked task version, each quadruplet was yoked to another quadruplet to serve as each other's foils (Bowman et al, 2021;de Araujo Sanchez and Zeithamova, 2023). This meant that the foil for each face was the same across all repetitions of the same trial type.…”
Section: Yoked Conditionmentioning
confidence: 99%
“…They found that participants who successfully made this generalization were also more likely to have worse memory for details of the learning experience (i.e., the context), compared to those who did not make this generalization 22 . Yet, this trade-off between generalization and detailed memory has not been consistently reported 24,25 and thus requires further investigation as to the parameters that drive this trade-off. In our study, we tested the following hypothesis: if the presence of conceptual knowledge promotes generalization during learning through episodic memory, it will impair the alternate function of episodic memory, to form detailed memories of that same information.…”
Section: The Relationship Between Memory Generalization and Detailed ...mentioning
confidence: 99%
“…Yoked condition. In the yoked task version, each quadruplet was yoked to another quadruplet to serve as each other's foils (Bowman et al, 2021;de Araujo Sanchez & Zeithamova, 2023). This meant that the foil for each face was the same across all repetitions of the same trial type.…”
Section: Procedures Differences Between Conditionsmentioning
confidence: 99%